Penerapan Qugamee (Quiz dan Game Edukasi) Interaktif pada Pembelajaran IPA-Fisika Menjadi Lebih Menyenangkan dengan Menggunakan Wordwall - Miftah Miftah; Chairunnisa Ar Lamasitudju (Universitas Tadulako, 2022)
The development of technology and learning media has a major impact on the teaching and learning process. One form of this development is the creation of a Wordwall application to support a more interesting learning process. This study aims to describe the application of interactive Qugamee using Wordwall and determine student responses to its application in science-physics learning. This research method uses the Waterfall model. The data obtained were analyzed quantitatively descriptively. The conclusion of this study is that the application of Qugamee using Wordwall makes learning more quality, more fun and interesting, can stimulate students' cognitive development, and students respond good to its application in science-physics learning.